Importing umbrellas: Most-Favored-Nation Clauses and Umbrella Clauses in Investment Arbitration - de la Flor Puccinelli, Nicolás (2020)
International Investment Law nowadays is characterized by fragmentation. This is mainly due to the different protection standards that States grant to foreign investors, as well as arbitration decisions in this regard. Although each protection standard must be analyzed in each specific case, international doctrine and Tribunals have recognized the existence of certain classic protection standards such as the Most-Favored-Nation Clauses or the so-called Umbrella Clauses. In this article, the authors seek to analyze the way in which these two protection standards usually operate and the possibility of invoking the benefits of the Umbrella Clause through the application of the Most-Favored-Nation Clause, according to what has been resolved by the international jurisprudence on the matter.